SEMANTICS AND FUNCTIONAL CHARACTERISTICS OF INTERROGATIVE SENTENCES IN MODERN FRENCH LANGUAGE (Scientific journal of the Fergana State University, 2023)
This article discusses the semantic and functional characteristics of interrogative sentences in modern French, specific aspects of interrogative sentences, the use of interrogative sentences as a means of communication, the establishment of a paradigm of the communicative type of interrogative sentences and explains their functional-semantic types in grammatical meaning.